2021
DOI: 10.1002/aepp.13190
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal farm labor and COVID‐19 spread

Abstract: The COVID‐19 pandemic in 2020 caused unprecedented shocks to agricultural food systems, including increased risk to worker health, labor‐related input costs, and production uncertainty. Despite employer precautions, there were numerous worksite outbreaks of COVID‐19. This paper examines the relationship between month‐to‐month variation in historical agricultural employment and changes in the incidence of confirmed COVID‐19 cases and deaths within U.S. counties from April to August 2020. The results show that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…These associations, found in the bivariate analysis, do not account for other variables, such as contacts with clients, the presence of TFW, the territory, and the quartile of the total number of workers, and therefore must be interpreted with caution. For the agriculture sector, even though the literature showed that workers in this sector have a higher positivity rate for SARS-CoV-2, 2,11 we did not find that the risk of identifying at least one outbreak was significantly different than for all the other EAS. It was surprising to note that the presence of TFWs in the agricultural sector did not seem to have an impact on the frequency of outbreaks of COVID-19 in that sector.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…These associations, found in the bivariate analysis, do not account for other variables, such as contacts with clients, the presence of TFW, the territory, and the quartile of the total number of workers, and therefore must be interpreted with caution. For the agriculture sector, even though the literature showed that workers in this sector have a higher positivity rate for SARS-CoV-2, 2,11 we did not find that the risk of identifying at least one outbreak was significantly different than for all the other EAS. It was surprising to note that the presence of TFWs in the agricultural sector did not seem to have an impact on the frequency of outbreaks of COVID-19 in that sector.…”
Section: Discussioncontrasting
confidence: 85%
“…Several studies have established that specific workplace characteristics are associated with a higher risk of COVID-19 cases and outbreaks. [1][2][3][4][5][6][7][8] In a cross-sectional descriptive study conducted at the beginning of the pandemic, the authors found that approximately 30% of COVID-19 cases among insured Italian workers were related to their workplace. 1 A few studies have documented high-risk economic sectors.…”
mentioning
confidence: 99%
“…3 e and f). The most prominent example was the outbreak in the region of Lleida between the first and second waves, a period characterised by the arrival of large numbers of seasonal farmers, which, according to the literature, could be related to COVID-19 outbreaks 50 . Among the different types of spatio-temporal interaction effects, the one that best fitted the data was the type II (Table 1 d), which assumes a RW1 for each area independent of the others.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic correlation between agricultural employment and COVID-19 growth rates was confirmed nationally using BLS’ Quarterly Census of Employment and Wages (QCEW) data by Charlton ( 2022 ), who showed that counties with 100 additional workers per month in fruit, vegetable, and horticultural employment in 2019 were associated with 4.5% more COVID-19 cases on average in 2020. Lusk and Chandra ( 2021 ) demonstrated that spatial correlations also held for death counts for agricultural workers and documented differences between rural and urban areas which could be used for public health intervention targeting.…”
Section: Introductionmentioning
confidence: 91%